Identification and differential expression dynamics of peach small GTPases encoding genes during fruit development and ripening - Falchi, Rachele (Oxford University Press, 2010)
The function of monomeric GTPases of the RAS superfamily in fruit development and ripening has been partially characterized. Here the identification of peach (Prunus persica) small GTPases of the RAS superfamily expressed in fruit and the characterization of their expression profiles during fruit development are described. Extensive searches on expressed sequence tag (EST) databases led to the selection of a total of 24 genes from peach encoding proteins with significant similarity to Arabidopsis small GTPases. Sequence similarity analyses and identification of conserved motifs, diagnostic of specific RAS families and subfamilies, enabled bona fide assignment of fourteen PpRAB, seven PpARF/ARL/SAR, two PpROP and one PpRAN GTPases. Transcriptional expression profiles of peach monomeric GTPases, analysed by real-time quantitative reverse transcription-PCR, were obtained for mesocarp samples, collected in two consecutive years. Reproducible patterns of expression could be identified for five peach RAB-encoding genes (PpRABA1-1, PpRABA2, PpRABD2-1, PpRABD2-2, and PpRABC2), two ARFs (PpARFA1-1 and PpARLB1), and two ROPs (PpROP3 and PpROP4). Interestingly, the transient transcriptional up-regulation of PpARF genes and of PpRAB genes of the A and D clades, putatively controlling the exocytic delivery of cell wall components and modifying enzymes, appeared to coincide with peaks of growth speed and sugar accumulation and with the final phases of ripening. To our knowledge, this is the first description of the co-ordinated differential expression of a set of genes encoding small GTPases of the ARF and RAB families which takes place during key moments of fruit development and maturation.